Duration of Remote Ischemic Conditioning and Outcome in Acute Ischemic Stroke - Yu Cui; Yi‐Ning Chen; Thanh N. Nguyen; Hui‐Sheng Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Remote ischemic conditioning has been found to be effective in improving functional outcomes in acute ischemic stroke. We conducted a post hoc analysis of the RICAMIS (Remote Ischemic Conditioning for Acute Moderate Ischemic Stroke) trial to determine whether long‐term remote ischemic conditioning duration after stroke onset is associated with better clinical outcomes in ischemic stroke. Methods and Results Patients from the full analysis set were included in this secondary analysis. The primary outcome was the proportion of patients with an excellent functional outcome at 90 days, defined as a modified Rankin Scale score of 0 to 1. Among the 1776 patients, there were 55 patients in the 1 to 7 days remote ischemic conditioning group, 345 in the 8 to 10 days group, 412 in the 11 to 13 days group, 51 in the 14 to 16 days group, and 913 in the control group. Compared with the control group, a significantly higher proportion of excellent functional outcomes at 90 days was found in the 11 to 13 days remote ischemic conditioning group (adjusted absolute difference, 9.1% [95% CI, 3.7%–14.5%]; P =0.001), which was attenuated in the other groups (adjusted absolute difference in the 8–10 days group, 2.0% [95% CI, −4.0% to 8.0%]; P=0.51; adjusted absolute difference in the 14–16 days group, 7.4% [95% CI, −5.8% to 20.5%]; P=0.27), but compared to the control group, there was lower proportion of excellent functional outcomes in the 1 to 7 days group (adjusted absolute difference, −14.4% [95% CI, −27.8% to 0.0%]; P=0.05). Conclusions Among patients with acute moderate ischemic stroke, a higher likelihood of excellent clinical outcome was found in patients with longer duration of remote ischemic conditioning.